Anaerobic gut fungi as biocatalysts: metabolic and physiological analysis of anaerobic gut fungi under diverse cultivation conditions - Schulz, Kevin Edward; Scholz, Dominik; Sikirić, Anto Rafael; Rambow, Daniela; Neumann, Anke; Ochsenreither, Katrin (Frontiers in Microbiology, 2025)
BackgroundAnaerobic gut fungi, known for their diverse carbohydrate-active enzymes and hydrogen production, have promising potential for the valorization of lignocellulosic materials. Despite being classified nearly 50 years ago and re-categorized into the phylum Neocallimastigomycota in 2007, their growth conditions and metabolism remain largely underexplored. This study investigates the metabolic responses of Aestipascuomyces dupliciliberans, Caecomyces churrovis, Khyollomyces ramosus, Orpinomyces joyonii, Pecoramyces ruminantium, and Neocallimastix cameroonii under various conditions, including different growth temperatures, wheat straw particle sizes, alternative carbon sources, and cultivation methods.ResultsStrain-specific differences were observed in temperature tolerance and metabolite production. Optimal growth occurred at 39 °C, while hydrogen production peaked at 41 °C in N. cameroonii, P. ruminantium, and C. churrovis. Larger wheat straw particles (2–3 mm) partially enhanced hydrogen yields, and soluble carbon sources such as glucose and cellobiose were efficiently metabolized, whereas xylose led to stress responses and low hydrogen output, particularly in K. ramosus and O. joyonii. High sugar concentrations triggered overflow metabolism, with increased lactate and formate production in A. dupliciliberans and N. cameroonii, while K. ramosus, lacking lactate dehydrogenase, accumulated formate and succinate. Fed-batch cultivation did not improve yields, likely due to substrate overfeeding and end-product inhibition. Biowaste substrates such as cucumber, carrot, and potato peels were effectively degraded and supported fungal growth. Notably, a novel morphological growth form was observed in O. joyonii under starvation conditions, suggesting a stress-induced developmental transition.ConclusionThis study provides valuable insights into the growth and physiology of anaerobic gut fungi and complements existing genomic data. The robustness of the process with respect to temperature, carbon source and substrate properties was evaluated, improving the understanding of anaerobic gut fungi cultivation and handling.